Mines Eight Hours Bill. Deputation to... Sir Matthew White Ridley... from the miners of Merthyr and Aberdare - Miners' Federation of Great Britain
Room 13, House of Commons, Tuesday, 18th February, 1896. - Transcript from the shorthand notes of Messrs. J. Moore and Son,...